Teacher Assessment in Increasing Students' Learning Independence in PAI Subjects - Aldila Winda Pramita; Nurmawati Nurmawati (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The purpose of the study was to analyze the condition of students' learning independence at SMPN 3 North Rantau, teacher assessment in improving students' learning independence in PAI subjects, and indicators of students' learning independence in class VIII-4. This research uses a qualitative research approach with a descriptive research type. The data collection techniques in this study were observation, interview, and documentation. The results showed that: (1) The condition of learning independence of students of SMPN 3 Rantau Utara is quite varied; some students already have independence in learning, and some are still less independent students. (2) The assessment carried out by PAI teachers in increasing students' learning independence is the use of appropriate learning and assessment methods, giving independent assignments, as well as formative assessments, assessments in discussions, and feedback. (3) Indicators of learning independence of students in class VIII-4 are confidence, responsibility, active in learning, and discipline in learning.